2016
DOI: 10.1016/j.jaac.2016.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of d-Methylphenidate, Guanfacine, and Their Combination on Electroencephalogram Resting State Spectral Power in Attention-Deficit/Hyperactivity Disorder

Abstract: Objective Psychostimulant medications are the gold standard of treatment for attention-deficit/hyperactivity disorder (ADHD); however, a significant minority (~30%) of individuals with ADHD fail to respond favorably. Noradrenergic agents are increasingly used as ADHD monotherapies or adjuncts for suboptimal stimulant response, yet knowledge of their cortical effects is limited. This study is the first to examine comparative effects of guanfacine (an alpha adrenergic 2A agonist), psychostimulant, and their comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 42 publications
1
41
0
Order By: Relevance
“…Beta activity increase tends to reflect brain cortical activity enhancement ( 29 ). In a previous QEEG study, methylphenidate treatment resulted in an increase in beta power in centro-parietal regions, which was correlated with behavioral and cognitive symptom improvement ( 30 ). It has been suggested that video game playing might stimulate synaptic dopaminergic transmission similar to methylphenidate stimulation in ADHD, which could result in attentional capacity enhancement ( 31 ).…”
Section: Discussionmentioning
confidence: 94%
“…Beta activity increase tends to reflect brain cortical activity enhancement ( 29 ). In a previous QEEG study, methylphenidate treatment resulted in an increase in beta power in centro-parietal regions, which was correlated with behavioral and cognitive symptom improvement ( 30 ). It has been suggested that video game playing might stimulate synaptic dopaminergic transmission similar to methylphenidate stimulation in ADHD, which could result in attentional capacity enhancement ( 31 ).…”
Section: Discussionmentioning
confidence: 94%
“…This study examines the baseline data of a subset of 246 children recruited from the UCLA community to participate in a clinical trial (Bilder et al., ; Loo et al., ; McCracken et al., ) (clinicaltrials.gov ID: NCT00429273). In a prior publication, we reported results based on 102 individuals from this dataset.…”
Section: Methodsmentioning
confidence: 99%
“…Of the 144 in the independent sample, five were excluded during our independent component analysis protocol (c.f., Appendix S2) and another 20 were excluded because task performance was less than our criterion of 60%. Full diagnostic details are provided in Supplemental Materials (c.f., Appendix S1) as well as in prior publications Loo et al, 2016;McCracken et al, 2016).…”
Section: Participantsmentioning
confidence: 99%
“…qEEG acquisition followed previously used procedures. 26 Participants underwent qEEG recording, including a five minute, eyes-open resting condition. Recordings were carried out using an Electrical Geodesics (EGI; Eugene, Oregon) GES300 system with 128-electrode high-impedance Hydrocel Geodesic Sensor Nets.…”
Section: Quantitative Electroencephalographymentioning
confidence: 99%